Synthesis and characterization of octamethyl- and methacrylate- polyhedral oligomeric silsesquioxanes (POSS) - Ong, Wei Jing. (2011)
This report documents the synthesis process and characterization results of polyhedral oligomeric silsequioxane (POSS) compounds. The synthesis of the polymerized methacrylate-POSS in this study is the purpose of its application as photoresist materials. Three types of hybrid inorganic–organic compounds, octamethyl-POSS, monofunctional and difunctional methacrylate-POSS were synthesized by the hydrolytic condensation process using methyltrimethoxysilane (MTMS) and (3-methacryloxypropyl)-trimethoxysilane (MPTMS) resins. The products were characterized by FTIR, 1H NMR, MALDI-TOF and DPC. The results showed that condensation has occurred for all three products. For the case of monofunctional and difunctional methacrylate-POSS, results shown that incompletely condensed POSS were generated. Polymerization of methacrylate-POSS was not attainable in this study. However, polymerization of the MPTMPS resin was successful when a higher UV beam intensity was used. This shows that increasing the light intensity can speed up the initiator photolysis and consequently aid in polymerization. Due to time constraint, the polymerization of methacrylate-POSS was not repeated using higher UV beam intensity. Therefore, the exotherms for photopolymerization can be further investigated by using the DPC. Furthermore, photoresist performances can be studied in terms of their sensitivity, contrast and pattern resolution.